2022
DOI: 10.29235/1814-6023-2022-19-1-38-47
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of remote ischemic postconditioning of the myocardium in rats with induced metabolic syndrome depends on the leptin level

Abstract: Remote postconditioning (RPost) has a great therapeutic potential for protecting the myocardium during ischemiareperfusion in clinical practice. At the same time, an important problem limiting the use of conditioning effects in the clinic is the presence of metabolic disorders in the patient. The aim of this work was to assess the effect of induced metabolic syndrome (iMetS) on the efficacy of the infarct-limiting effect of remote ischemic postconditioning (RPost) in rats and to study the mechanisms of this ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…We tried evaluating the role of the autonomic nervous system in RPost. Rats were subjected to CAO (45 min) and reperfusion (2 h) [ 20 ]. RPost was induced by the repeated I/R of hindlimbs.…”
Section: Experimental Datamentioning
confidence: 99%
See 3 more Smart Citations
“…We tried evaluating the role of the autonomic nervous system in RPost. Rats were subjected to CAO (45 min) and reperfusion (2 h) [ 20 ]. RPost was induced by the repeated I/R of hindlimbs.…”
Section: Experimental Datamentioning
confidence: 99%
“…We found that blocking peripheral opioid receptors completely abolished the infarct-reducing effect of RPost induced by hind limb I/R in rats [ 20 ]. It was detected that opioid peptide deltorphin II can mimic RPost [ 30 , 31 ].…”
Section: Experimental Datamentioning
confidence: 99%
See 2 more Smart Citations
“…В данном исследовании мы не обнаружили стати стически значимого снижения размера инфаркта мио карда у крыс с МетС. Это согласуется с данными, полу ченными в экспериментах на самцах крыс Вистар, по лучавших ВУВЖД, аналогичную используемой в данном исследовании [9]. T. Thim и соавт.…”
Section: о б с у ж д ен и еunclassified